Analisis Daya Saing dan Faktor-faktor yang Mempengaruhi Ekspor Produk Alas Kaki Indonesia ke Amerika Serikat Ditinjau Dalam Perspektif Ekonomi Islam - Nur Laili (Jurnal Ilmiah Ekonomi Islam, 2021)
Footwear is one of Indonesia's leading export commodities. However, this achievement is still far from the target set by the Indonesian Ministry of Industry, namely growth of 10% annually. The aim this study are to analysis of Indonesia's competitiveness of footwear products exported to the United States, factors affect Indonesian footwear exports to the US and the Islamic economy view competitiveness and the factors affecting exports. The method used is a quantitative method. Using the RCA analysis and multiple linear regression analysis. The data taken from this research is secondary data. The results showed that the RCA index>1, then the export of Indonesian footwear products to the US was competitive in the world. Partially, US GDP and the exchange rate have a positive and significant effect on Indonesian footwear exports to the US, prices have a positive and insignificant effect on Indonesian footwear exports to the US, and production has a negative and insignificant effect on Indonesian footwear exports to the US. Simultaneously, US GDP, exchange rates, prices and production together influence the export of Indonesian footwear to the US. Competition from an Islamic economic perspective is highly recommended, but it must be healthy as explained in Q.S Al-Baqarah:148 where every country is prohibited from committing fraud, one of which is the dumping technique. Keywords: RCA, US GDP, Exchange Rates, Prices, Production, Footwear Exports, Islamic Economic Perspective.